PENGARUH ETOS KERJA, DISIPLIN KERJA, FASILITAS KERJA DAN KOMPETENSI PEGAWAI TERHADAP PENGEMBANGAN PEGAWAI DI KANTOR PELAYANAN PAJAK PRATAMA MEDAN TIMUR - Abdi Timor; Bistok Siagian; Dede Sahputra; Heny Lestari; Ikhsan Amri Parinduri (JRMB (Jurnal Riset Manajemen & Bisnis), 2021)
The problems in this research are: How is the influence of work ethic, work discipline, work facilities and employee competence partially and concurrently on the employee development in the Kantor Pelayanan Pajak Pratama Medan Timur? Research objectives: To determine the effect of work ethic, work discipline, work facilities and employee competence partially and simultaneously on the employee development in the Kantor Pelayanan Pajak Pratama Medan Timur. The hypothesis proposed is: There is a significant effect of work ethic, work discipline, work facilities and employee competence partially and jointly on the employee development in the Kantor Pelayanan Pajak Pratama Medan Timur. The study was conducted at the Kantor Pelayanan Pajak Pratama Medan Timur Jalan Sukamulia Nomor 17A, Kota Medan, Provinsi Sumatera Utara, kode pos 20152, with a population of 98 people, and a study sample of 52 people. The data resources used primary data that obtained by distributing questionnaires, interviews, and documentation, which tested by IBM Statistics 24 for Windows. Based on the analysis results obtained work ethic has a not effect on the employee development of the Kantor Pelayanan Pajak Pratama Medan Timur, this is supported by the results of t count analysis t-table (1,251 2,011) at n = 52 at 95% significance level. Work discipline has a positif and significant effect on the employee development of the Primary Tax Service Office of Medan Timur, this is supported by an analysis of t count t-table (2,883 2,011) at n = 52 at 95% significance level. Work facilities has a not effect on the employee development of the Kantor Pelayanan Pajak Pratama Medan Timur, this is supported by an analysis of t count -table (1,361 2,011) at n = 52 with a significant level of 95%. Employee competence has a effect on the employee development of the Kantor Pelayanan Pajak Pratama Medan Timur, this is supported by an analysis of t count -table (3,629 2,011) at n = 52 with a significant level of 95%. Value of F-count F table (21,023 2,57) This states that together (multiple) there are positive and significant effects of work ethic, work discipline and work facilities on the employee development of employees of the Kantor Pelayanan Pajak Pratama Medan Timur . Thus the hypothesis proposed is accepted by the truthÂ